LATE DEVONIAN INDEX BRACHIOPODA OF NORTH-EAST ESFAHAN IN CORRELATION WITH OTHER REGIONS (Journal of Sciences, Islamic Republic of Iran)
Abundance and multilateral extension of prominent genus and species of Brachiopoda in the majority of sedimentation series of the Late Devonian have been observed in all parts of Iran. The variability and rapid change in this respect has made it possible to delineate different lines of orthogenetism, biozonation and present biostratigraphical models at the sub-stage level. These characteristics have prompted this study on the external character, biometry and internal properties of specimens to provide a taxonomy and comparison of genus, species and subspecies of the Late Devonian Brachiopoda in different parts of Iran, especially in north of Esfahan, Abadeh region, north of Kerman, south-east of Anarak, Shotori Range, Central Alborz, Damghan, and Shahrud regions. In the orders Spiriferida, Rhynchonellida, Strophomenida, and Orthida, many genera and species can be identified and their stratigraphical expansion and geographical situation can be compared. The study has involved ten genera and species of Rhynchonellida, ninety genera and species of Spiriferida, twelve species and subspecies of Strophomenida, and two genera of Orthida.